Upaya Pengendalian Respon Emosional Pasien Hipertensi dengan Terapi Musik Dominan Frekuensi Sedang - Asrin,; Mulidah, Siti; Triyanto, Endang (Jurusan Keperawatan FIKES UNSOED, 2009)
Music has an effect to the physical and emotional responses. Music was utilized for the therapeutic intervention since the middle of 20th century that was appeared in many kinds of cultures. Recently, the use of music for the intervention had been developed rapidly. Music can touch the level of awareness, physic, psychology, and social. Otherwise, there is no a report of study that discussed of an effort to control the emotional responses for the primary hypertension patients. The method of this study was utilized an experiment study by using non static pretest-posttest control group design. This study was conducted in the area of Public Health Centre of East Purwokerto, Banyumas Regency. Populations of this study were primary hypertension patients who were living in the area of Public Health Centre of East Purwokerto, Banyumas Regency. The respondents were chosen as randomly method. The respondents were divided into 2 groups, which were intervention and control group. The intervention group was primary hypertension patients who were fulfilling the inclusion criteria. The control group was primary hypertension patients who were voluntary registered as a respondent. The number of respondent for each group was 30 respondents. The result of this study shows that the music therapy by utilizing of middle frequency dominantly (750 – 3000 Hz) could control the emotional responses of primary hypertension patients. Statistically, the blood pressure of the intervention and the control group was different significantly. The data analysis by t test show that t-value -12.870 and p-value 0.000. The data analysis of respiration show t-value -8,374 and p-value 0.000. The data analysis by U-Mann Whitney Test shows the counted value 6 and p-value 0.000 for pulse and the counted value 285 and p-value 0.000 for the temperature of body. The duration of intervention for achieving of blood pressure normal value was majority in 1 day (56%) and minority in 5 days (6.6%). The kinds of music that were chosen by respondents were memorial song, keroncong song, and campursari song . The music therapy of middle frequency dominantly (750 – 3000 Hz) could control the emotional responses (blood pressure, pulse, respiration, and body temperature) of primary hypertension patients in 1 to 5 days intervention. Every song that was played for the intervention was a requested by patients.